Schools at war a story of education, evacuation and endurance in the Second World War - Stranack, David (Phillimore, 2005)
Schools at War marks the first time that the extraordinary tales of evacuation, improvisation, drama, and trauma experienced by many English schools during the Second World War have been collected into a single book. This remarkable achievement was made possible by the Association of Representatives of Old Pupils' Societies (AROPS). Founded in 1971, this group of old boys' and old girls' organizations now has more than 260 members. AROPS decided to conduct a survey to discover what actually happened to its members' Alma Maters during the years 1939 to 1945. Although the original survey only sought to track the movements of schools during the war years, the request for information was responded to with such enthusiasm that a wealth of historical material was gathered. Schools at War chronicles the stories that emerged. It contains an amazing diversity of experiences-from schools in the heart of the country who were virtually untouched by the global conflict, to the schools in England's towns and cities, whose staff suffered the knowledge that, after the previous night's air raids, they would not be seeing some of their pupils again. The schools' stories are of hard work, commitment, bravery, doggedness-and often humor. Above all this, however, they share a determination that they would not be beaten. This compelling and fascinating narrative will appeal to those who have a connection to one of the schools, and to anyone with an interest in modern social history.